ART outcomes of patients in women with Isolated Hypogonadotropic Hypogonadism: a retrospective study in China - Wanxue Xu; Rong li; Jie Qiao (BMC, 2023)
Abstract Background Isolated Hypogonadotropic Hypogonadism (IHH) is a rare reproductive disorder caused by the dysfunction of the gonadotropin-releasing hormone axis. Patients with IHH typically fail to enter or develop through puberty and retain infertile without an exogenous hormone supplement. This study aimed to investigate the population characteristics and reproductive outcomes in IHH patients undergoing assisted reproductive technology (ART) treatment, and evaluate the best-performed predictor for ovarian response and clinical pregnancy in patients with IHH. Methods This retrospective cohort study included 83 women with IHH who underwent fresh ART cycles and non-diagnosed controls (n = 676). The receiver operating characteristic curves were generated to assess the predictor for the ovarian response. Logistic regression analyses were performed to investigate the independent factors for clinical pregnancy in IHH. Results The basal hormone levels were significantly lower in the IHH group compared to the control group. The fertilization rate and 2PN rate were significantly higher in IHH groups, as was the number of transferable embryos. The study identified that AMH was the best predictor of high ovarian response in IHH, with an AUC of 0.767 (0.573, 0.961). Conversely, the follicle-to-oocyte index (FOI) exhibited the highest AUC of 0.814 (0.642, 0.985) for predicting low ovarian response. Based on FOI values, the IHH patients were divided into two groups, and the study found a significant increase in clinical pregnancy rate (43.8%, 58%; P < 0.001) and live birth rate (37.5%, 58%; P < 0.001) from the low FOI to the normal FOI groups. Moreover, the number of oocytes retrieved, fertilized embryos/rate, 2PN embryos/rate, and number of excellent quality embryos were significantly higher in the normal FOI group (P < 0.001 or P = 0.005) than in the low FOI group. Logistic regression analyses revealed FOI to be the independent factor affecting clinical pregnancy in IHH patients. Conclusions The study findings suggest that patients with IHH were good responders to IVF treatment. Although AMH was the best-performed predictor for the high ovarian response, FOI had the best capability in predicting the low ovarian response. FOI was an independent factor affecting clinical pregnancy in IHH undergoing IVF/ICSI.